2020
DOI: 10.1088/1748-9326/abb330
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous knowledge on climate change adaptation: a global evidence map of academic literature

Abstract: There is emerging evidence of the important role of indigenous knowledge for climate change adaptation. The necessity to consider different knowledge systems in climate change research has been established in the fifth assessment report (AR5) of the Intergovernmental Panel on Climate Change (IPCC). However, gaps in author expertise and inconsistent assessment by the IPCC lead to a regionally heterogeneous and thematically generic coverage of the topic. We conducted a scoping review of peer-reviewed academic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 63 publications
5
95
0
8
Order By: Relevance
“…Published IKS-based adaptation strategies in developing world context are predominantly from the African and Asian continents, with only a few from South America and Oceania (Figure 2). This reflects the documented geographical gap in IKS-based climate change adaptation research found in other systematic reviews, with northern and central Africa, northern Asia, South America, Greenland, and Australia being underrepresented while the research clusters around Sub-Saharan East Africa, the Tibetan plateau, and the North American Arctic [17,20,21]. For example, of the 236 articles reviewed in their global evidence map paper that had a broader scope than this current systematic review, 92 were from Africa, 75 from Asia, 31 from Australasia and small island states, 26 from North America, and 12 from Central and South America [17].…”
Section: Overview Of the Reviewed Articlesmentioning
confidence: 87%
See 1 more Smart Citation
“…Published IKS-based adaptation strategies in developing world context are predominantly from the African and Asian continents, with only a few from South America and Oceania (Figure 2). This reflects the documented geographical gap in IKS-based climate change adaptation research found in other systematic reviews, with northern and central Africa, northern Asia, South America, Greenland, and Australia being underrepresented while the research clusters around Sub-Saharan East Africa, the Tibetan plateau, and the North American Arctic [17,20,21]. For example, of the 236 articles reviewed in their global evidence map paper that had a broader scope than this current systematic review, 92 were from Africa, 75 from Asia, 31 from Australasia and small island states, 26 from North America, and 12 from Central and South America [17].…”
Section: Overview Of the Reviewed Articlesmentioning
confidence: 87%
“…Indeed, reviews of climate change adaptation in the developing world exist, but only a few have considered indigenous knowledge systems. For example, [16] discussed the status of climate change adaptation in Africa and Asia while [17] provided a global evidence map of indigenous knowledge's deployment to climate change adaptation. The former requires updating while the latter requires more in-depth focus on countries in the developing world because of their unique context, which includes their higher vulnerability to climate change and lesser capacity to adapt to its impact.…”
Section: Introductionmentioning
confidence: 99%
“…Following this approach, we designed our Google Scholar search accordingly and carried it out between May and July 2020. Our search method approximates that used by Petzold et al (2020) and others, adapted to the limitations imposed by our lack of external resources.…”
Section: Literature Searchmentioning
confidence: 99%
“…Canosa et al (2020) thought that climate adaptation is a priority for Arctic regions that suffer more from climate change globally, and they suggested that adaptation should be a central component of climate policy [34]. Petzold et al studied the role of indigenous knowledge on climate change adaptation through a global evidence map of academic literature, and their results showed that there are adaptation knowledge gaps in northern and central Africa, South America, northern Asia, Australia, and urban areas [35]. Ledda et al found out that the current climate adaptation plan in many regions could not fully work because of failing to include key adaptation sectors and actions [36].…”
Section: Literature Reviewmentioning
confidence: 99%